Study of the Sensory Acceptance, Physical Properties and Microbial Analysis for Wheat Bread Enriched with Ginger and Black Pepper - Asman, Saliza (Enhanced Knowledge in Sciences and Technology, 2022)
This work present the studies on the enrichment of wheat bread with ginger and black pepper. The analyses of sensory acceptance, physical properties and microbial growth were explored. Four samples of enriched wheat bread were prepared which are non-enriched wheat bread (F1) as control, wheat bread enriched with black pepper only (F2), wheat bread enriched with ginger only (F3) and wheat bread enriched with ginger and black pepper (F4). The sensory analysis indicated that the F4 sample (4.400 ± 1.5128) has affected consumers’ acceptance with the least sensorial acceptability. The colour mean values (L*= 40.86 ± 1.0750, a* = 7.34 ± 0.1457 and b* = 20.70 ± 0.7770) and the highest texture mean value (543.947 ± 3.2745) of F4 sample respectively demonstrated that the ginger and black pepper influenced the enriched wheat bread colour and texture characteristics. The water activity (0.815 ± 0.0086) and moisture content (43.85 ± 0.5255) of the F4 sample were low. In microbiological analysis, F4 has the highest fungi count (3.7 x 107 cfu/mL) and kept increasing exceeded to 300 colonies than other samples at day 4 of storage. It can be concluded that the addition of ginger and black pepper to the wheat bread affects the wheat bread quality in terms of its sensory acceptance, physical properties and microbial growth.